2021
DOI: 10.7759/cureus.18523
|View full text |Cite
|
Sign up to set email alerts
|

Breast Apocrine Carcinoma Detected Incidentally as Axillary Lymphadenopathy in a CT Scan

Abstract: Breast apocrine cell pathology varieties include benign papilloma, non-high-grade apocrine ductal carcinoma in situ (DCIS), and breast invasive apocrine carcinoma (BAC). BAC is a rare type of invasive breast cancer and is histologically distinguished by large-sized cells with copious eosinophilic granular cytoplasm, round nuclei, and prominent nucleoli. Its prognosis is similar to breast invasive ductal carcinoma, of no special type (IDC-NST), when matched for tumour stage and histological grade. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The breast apocrine glands secrete fat droplets into breast milk where those in the skin and eyelid are sweat glands. Apocrine carcinoma of the breast is a rare form of malignancy mainly affecting women, however, it can develop in men also [4]. It is seen more frequently in the age group (50-79), some studies indicated a higher rate of apocrine carcinoma (and AR expression) in the elderly and also a tendency of lower rates seen in white women [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breast apocrine glands secrete fat droplets into breast milk where those in the skin and eyelid are sweat glands. Apocrine carcinoma of the breast is a rare form of malignancy mainly affecting women, however, it can develop in men also [4]. It is seen more frequently in the age group (50-79), some studies indicated a higher rate of apocrine carcinoma (and AR expression) in the elderly and also a tendency of lower rates seen in white women [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that between 0.5-4% of all breast cancers belong to this type, however, Malley and Bane in 2012, stipulated that such variability is likely to be due to a lack of well-defined diagnostic criteria. Currently, it is regarded as a specific form of breast invasive ductal carcinoma of no special type that primarily involves the milk ducts and migrates to other parts of the breast [4]. The characteristic apocrine pattern of the tumour cells may show abundant eosinophilic granular cytoplasm and prominent multiple nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…IDC refers to the neoplastic proliferation and microinvasion of luminal epithelial cells into surrounding breast stroma, by passage through the ductal wall [ 5 ], following the disruption of the ductal basement membrane and myoepithelial cell layer. Based on the histological proprieties of tumors, several subtypes of IDC have been described [ 28 ]: the classical nonspecific subtype/not otherwise specified subtype (IDC-NST/IDC-NOS) [ 5 ], breast invasive apocrine carcinoma (BAC) [ 29 ], medullary carcinoma of the breast (MBC) [ 30 ], mucinous carcinoma/colloid carcinoma (MCB) [ 31 ], invasive papillary carcinoma (IPC), invasive micropapillary carcinoma (IMPC), and tubular ductal carcinoma (TC). Synthetically, IDCs can be classified as ”no special type” because these tumors do not emphasize sufficient morphological characteristics to be classified as a distinct histological type, and ”special type” that present specific cellular and molecular landscapes [ 32 ].…”
Section: Differentiating Idc From Other Bcsmentioning
confidence: 99%